Cytokinin Deficiency Alters Leaf Proteome and Metabolome during Effector-Triggered Immunity in Arabidopsis thaliana Plants - Pan, Ling; Berka, Miroslav; Černý, Martin; Novák, Jan; Luklová, Markéta; Brzobohatý, Břetislav; Saiz-Fernández, Iñigo (Plants (Basel, Switzerland), 2022)
The involvement of cytokinins (CK) in biotic stresses has been recognized, while knowledge regarding the effects of CK deficiency on plant response against pathogens is less abundant. Thus, the purpose of this study was to reveal the effects of CK deficiency on proteomics and metabolomic responses of flg22-triggered immunity. We conducted a series of histochemical assays to investigate the activity of the downstream pathways caused by flg22, such as accumulation of ROS, induction of defence genes, and callose deposition, that occurred in Arabidopsis thaliana transgenic lines overexpressing the Hordeum vulgare CKX2 gene (HvCKX2), which are therefore CK-deficient. We also used GC and LC-MS-based technology to quantify variations in stress hormone levels and metabolomic and proteomic responses in flg22-treated HvCKX2 and wild-type Arabidopsis plants. We found that CK deficiency alters the flg22-triggered plant defence response, especially through induction of callose deposition, upregulation of defence response-related proteins, increased amino acid biosynthesis, and regulation of plant photosynthesis. We also indicated that JA might be an important contributor to immune response in plants deficient in CKs. The present study offers new evidence on the fundamental role of endogenous CK in the response to pathogens, as well as the possibility of altering plant biotic tolerance by manipulating CK pools.
Keywords: metabolome; Flg22 peptide; Arabidopsis thaliana; defence response; cytokinin; proteome